Emotion regulation therapy for cancer caregivers—an open trial of a mechanism-targeted approach to addressing caregiver distress. Issue 2 (5th November 2018) - Applebaum, Allison J; Panjwani, Aliza A; Buda, Kara; O'Toole, Mia S; Hoyt, Michael A; Garcia, Adam; Fresco, David M; Mennin, Douglas S
Abstract: Informal caregivers (ICs) are integral to care provided to patients facing life-threatening or incurable illnesses. This responsibility causes considerable burden, as approximately one half of ICs report clinically significant symptoms of depression and/or anxiety that persist when left untreated. Psychosocial interventions containing efficacious treatment principles (e.g., cognitive behavior therapy [CBT]) show disappointing results in reducing anxiety and depression in ICs. This may reflect failure of these interventions to specifically target crucial mechanisms underlying the central feature of distress caused by the patient's illness—notably, perseverative negative thinking (PNT). Emotion Regulation Therapy (ERT) is an efficacious CBT developed to explicitly target mechanisms underlying PNT and the emotional concomitants that arise in response to stressful situations. This open trial was conducted to evaluate the acceptability and initial efficacy of ERT adapted to the experience of cancer ICs (ERT-C). Thirty-one ICs provided informed consent and completed eight weekly individual sessions of ERT-C. Participants completed self-report measures of depression and anxiety symptoms, PNT, emotion regulation deficits, and caregiver burden before and after treatment. ERT-C was well tolerated as indicated by 22 treatment completers and feedback provided in exit interviews. ICs demonstrated reduced depression and anxiety symptoms, PNT, and emotion regulation deficits with moderate to large effect sizes (Hedge's g range: 0.36–0.92). Notably, caregiver burden was not reduced but ICs expressed more ability to confront caregiving-related challenges. Findings offer promising but preliminary support for ERT-C as a conceptual model and treatment modality for distressed cancer ICs. Abstract : Emotion Regulation Therapy (ERT) was well tolerated and demonstrated reduced depression, anxiety, perseverative negative thinking, and emotion regulation deficits in distressed cancer caregivers.